Diversity of fauna species in the mangrove ecosystem of Youtefa Bay Tourism Park, Papua, Indonesia (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Sari A, Tuwo A, Saru A, Rani C. 2022. Diversity of fauna species in the mangrove ecosystem of Youtefa Bay Tourism Park, Papua, Indonesia. Biodiversitas 23: 4490-4500. Youtefa Bay Tourism Park is a mangrove ecosystem in Jayapura City, Papua, Indonesia with high importance for biodiversity conservation as well as providing livelihood for local communities. Yet, information regarding the biological diversity of the mangrove ecosystem is lacking. This information is important to assess the state of the mangrove and to support its sustainable management of this area. This research aimed to determine the faunistic diversity of Youtefa Bay Tourism Park. The research was conducted from August 2019 to February 2020 using line transect method with quadrant to record species and the number of individuals. The results showed that in the studied area there were six, five and 27 species of birds, reptiles and macrozoobenthos, respectively. The density of birds ranged from 2.35-23.94 ind/ha with Sterna hirundo of the Sternidae family having the highest density. The reptile species density ranged between 20 and 66.67 ind/ha, while the most common macrozoobenthos species were from Gastropoda and Pelecypoda classes. The highest and lowest relative abundance for birds were S. hirundo and Sula lencogastes with 20% and 5%, while that of reptiles were Mabouya sp. and Varanus salvadorii with 37% and 15%, and for macrozoobenthos species were Duplicaria duplicata and Solen sp. with 9.93% and 0.35%, respectively. The Diversity Index (H’) of birds, reptiles, and macrozoobenthos ranged of 0.29-1.39, 0.27-1.61, and 2.92-3.04, respectively. The diversity index was as low at Abepantai and Youtefa Bay Pier, while moderate at Tobati, Enggros, and Nafri Villages. Water quality parameters indicated that the waters in Youtefa Bay Tourism Park were still suitable for the survival of biota and the preservation of the mangrove ecosystem. The results of this study might be useful for monitoring the status of the mangrove ecosystem in the future and for baseline information in developing sustainable management of Youtefa Bay Tourism Park.
Keywords: Community Distribution, Diversity, Fauna Species, Youtefa Bay